Al-Maturidi and the development of Sunni theology in Samarqand - Rudolph, Ulrich. (Islamic History and Civilization, 2015)
Al-Māturīdī (d. 944 CE), the prominent Hanafi scholar from Samarqand, succeeded in formulating a theological doctrine which is widely accepted in Sunni Islam to this day. The present volume which is a revised English translation of the German original published in 1997 examines his teachings by describing their principal characteristics and situating them in the history of kalām. Part one investigates the development of Hanafi thought in Transoxania before Māturīdī's time. Part two deals with the other religious groups (in particular the Mu'tazilites) which emerged in this area during his lifetime. Part three shows how he explained and defended the position of his predecessors; in doing so, he reformed their traditional views, thereby developing his own theology which then became the basis of a new tradition, viz. the Māturīdite school.